Pediatric Emergency Medicine Simulation Curriculum: Cardiac Tamponade - Julie A. Augenstein; Jason Deen; Anita Thomas; Emily Moser; Kimberly Stone; Jennifer Reid; Rebekah Burns (Association of American Medical Colleges, 2018)
Introduction Cardiac tamponade is an uncommon presentation to the pediatric emergency department and requires early recognition and emergent intervention. Methods We developed this patient simulation case to simulate a low-frequency, high-acuity scenario for pediatric emergency medicine fellows and resident physicians in emergency medicine, pediatrics, and family medicine. We ran the case in a pediatric emergency department using a high-fidelity pediatric mannequin and equipment found in the clinical environment, including a bedside ultrasound machine. The case involved a 10-year-old patient with Hodgkin lymphoma who presented with fever, neutropenia, and shock and was found to have a pericardial effusion with tamponade after evaluation. The providers were expected to identify signs and symptoms of shock, as well as cardiac tamponade, and demonstrate appropriate emergent evaluation and management. Required personnel included a simulation technician, instructors, and a nurse. Debriefing tools tailored specifically for this scenario were created to facilitate a formal debriefing and formative learner assessment at the end of the simulation. Results This case has been implemented with 10 pediatric emergency medicine fellows during two 3-year cycles of fellow education. Session feedback reflected a high level of satisfaction with the case and an increased awareness of bedside ultrasound in the identification of cardiac tamponade. Discussion This resource for teaching the critical components for diagnosing and managing unstable cardiac tamponade in the pediatric patient, including use of bedside ultrasound, was well received by pediatric emergency medicine fellows.